Certificate Institution Activity System sebagai Penunjang Positive Legal Soft-Skill dalam Job Acceptance - Moh. Rif'an; Misael Avemnasal Sitepu; Hary Stiawan (CV Rewang Rencang, 2020)
The problem in the implementation of education is a serious problem, where errors that can be concluded in education problems will cause internal damage to the nation that can be monitored through HDI (Human Development Index). But the problem is the existence of an elderly society productive school but does not have a level of education or homelessness education. In this paper, the author initiated Legal Soft Skills Certification as a form of implementation of the Article 31 paragraph 2 and Article 28 C paragraph 1 of the Indonesia Constitution and its amendments. In order to emerge an alternative path for homeless people to regain their right to self-development through basic needs, get education and benefit from science and technology to improve their quality of life.